THE IMPACT OF VARYING WEIGHT FRACTIONS ON THE PHYSICOMECHANICAL PROPERTIES OF COMPOSITES REINFORCED WITH NEWBOULDIA LAEVIS FIBER PARTICLES - Chikelu, P. O.; Akpan, W. A.; Obot, O. W. (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2024)
The growing awareness of environmental protection has sparked interest in researching plant-based particulate materials as sustainable alternatives to synthetic materials for reinforcing polymer composites. However, there is limited literature on how to optimize the properties of these natural particle-reinforced polymer composites. In this study, we fabricated and characterized polymer composites with different weight fractions of treated Newbouldia fibre particles as reinforcements. We evaluated the behaviour of these composites in terms of water absorption, mass density, impact strength, flexural strength, and compressive strength based on varying weight fractions using standard methods. The results showed that water absorption increased while mass density decreased with higher weight fractions of fibre particles. The impact strength exhibited inconsistent behaviour, initially increasing, then decreasing, and finally increasing again as the weight fraction rose. Meanwhile, flexural strength decreased, whereas compressive strength increased with higher weight fractions. These findings were confirmed through regression analysis, indicating that the weight fraction of fiber particles significantly affects the water absorption, mass density, impact strength, flexural strength, and compressive strength of Newbouldia laevis fibre particle-reinforced polyester composites. Therefore, when designing composite materials, it is essential to vary the weight fraction to optimize the properties of the polymer composite for lightweight applications.